Glucocorticoids inhibit activation-induced cell death (AICD) via direct DNA-dependent repression of the CD95 ligand gene by a glucocorticoid receptor dimer - Baumann, Sven; Schmid, Wolfgang; Krammer, Peter H.; Schütz, Günther (Blood, 2005)
Glucocorticoids (GCs) play an important role in the regulation of peripheral T-cell survival. Their molecular mechanism of action and the question of whether they have the ability to inhibit apoptosis in vivo, however, are not fully elucidated. Signal transduction through the glucocorticoid receptor (GR) is complex and involves different pathways. Therefore, we used mice with T-cell-specific inactivation of the GR as well as mice with a function-selective mutation in the GR to determine the signaling mechanism. Evidence is presented for a functional role of direct binding of the GR to 2 negative glucocorticoid regulatory elements (nGREs) in the CD95 (APO-1/Fas) ligand (L) promoter. Binding of GRs to these nGREs reduces activation-induced CD95L expression in T cells. These in vitro results are fully supported by data obtained in vivo. Administration of GCs to mice leads to inhibition of activation-induced cell death (AICD). Thus, GC-mediated inhibition of CD95L expression of activated T cells might contribute to the anti-inflammatory function of steroid drugs. (Blood. 2005;106:617-625)
Gesehen am 04.03.2021